2003
DOI: 10.1074/jbc.m210321200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Tumor Endothelium Marker 8 Cytoplasmic Tail-independent Anthrax Toxin Binding, Proteolytic Processing, Oligomer Formation, and Internalization

Abstract: The interaction of anthrax toxin protective antigen (PA) and target cells was assessed, and the importance of the cytosolic domain of tumor endothelium marker 8 (TEM8) in its function as a cellular receptor for PA was evaluated. PA binding and proteolytic processing on the Chinese hamster ovary cell surface occurred rapidly, with both processes nearly reaching steady state in 5 min. Remarkably, the resulting PA63 fragment was present on the cell surface only as an oligomer, and furthermore, the oligomer was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
190
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 136 publications
(201 citation statements)
references
References 39 publications
9
190
2
Order By: Relevance
“…This finding is consistent with an interaction between the carboxyl group of Asp 683 and the metal coordination site of the anthrax receptors, TEM8 and CMG2. Recent studies in our laboratory have shown that the extracellular domain and a transmembrane domain or membrane anchor are necessary for PA activity, whereas the cytoplasmic tail is not essential (6). The extracellular portions of the receptors contain a von Willebrand factor type A domain with a metal ion-dependent adhesion site (MIDAS) motif.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with an interaction between the carboxyl group of Asp 683 and the metal coordination site of the anthrax receptors, TEM8 and CMG2. Recent studies in our laboratory have shown that the extracellular domain and a transmembrane domain or membrane anchor are necessary for PA activity, whereas the cytoplasmic tail is not essential (6). The extracellular portions of the receptors contain a von Willebrand factor type A domain with a metal ion-dependent adhesion site (MIDAS) motif.…”
Section: Discussionmentioning
confidence: 99%
“…RAW264.7, a mouse macrophage cell line, was grown in Dulbecco's modified Eagle's medium with 10% fetal bovine serum, 10 mM HEPES, 2 mM Glutamax I, and 50 g/ml gentamycin. CHO cell clone 6 (CHO-CL6) and a furin-deficient cell line, CHO FD11, were previously described (6,31) and were grown in ␣-minimal essential medium supplemented with 10% fetal bovine serum, 10 mM HEPES, 2 mM GlutaMax I, and 50 g/ml gentamycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PA is synthesized as an 83-kDa protein (PA 83 ) for which two cell surface receptors have been identified: tumor endothelial marker 8 (TEM8) (2,3) and capillary morphogenesis protein 2 (CMG2) (4). Two splice variant mRNAs derived from the TEM8 gene (sv1 and sv2) encode functional anthrax toxin receptors (2,5). TEM8 expression has been documented in epithelium of the lung, intestine, and skin, the three routes of entry in anthrax infection (6).…”
mentioning
confidence: 99%
“…Cells and Culture Media-Parental wild type CHO cells (CHO WTP4) and the PA receptor-expressing CHO CMG2-C4 and CHO TEM8-T4 cells, which overexpress CMG2 and TEM8, respectively, are as described previously (26,30). CHO cells were grown in minimum essential medium ␣ with 5% FBS, 2 mM glutamine, 5 mM HEPES, pH 7.4, and 50 g/ml gentamicin, with or without 300 g/ml hygromycin B. HeLa cells were cultured in Dulbecco's modified Eagle's medium with 10% FBS, 2 mM glutamine, and 50 g/ml gentamicin.…”
Section: Methodsmentioning
confidence: 99%